1984
DOI: 10.1136/thx.39.10.780
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary disease in patients with Marfan syndrome.

Abstract: Hospital case notes and chest radiographs of 100 patients with Marfan syndrome were investigated for evidence of pulmonary disease. The criteria for inclusion of details of a given patient in the study were the occurrence of Marfan abnormalities in at least two separate body systems (skeletal, cardiovascular, ocular)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 9 publications
(1 reference statement)
2
85
0
6
Order By: Relevance
“…53 Such bullae (or blebs) can predispose to spontaneous pneumothorax. Symptoms of pneumothorax include sudden onset of chest pain, dyspnea, and/or cyanosis.…”
Section: Pulmonary Issues Encountered Inmentioning
confidence: 99%
“…53 Such bullae (or blebs) can predispose to spontaneous pneumothorax. Symptoms of pneumothorax include sudden onset of chest pain, dyspnea, and/or cyanosis.…”
Section: Pulmonary Issues Encountered Inmentioning
confidence: 99%
“…60 Spontaneous pneumothorax occurs in 4 -11% of patients and may be associated with apical bullae. 61,62 Recurrence is common, and there should be a low threshold for surgical intervention. Mechanical ventilation can exacerbate respiratory difficulties in Marfan neonates because of susceptibility to pneumothorax, bullae and emphysema.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…An increased occurrence of pneumothorax especially in males has been reported with incidence up to 40% (31). Pneumothorax is more likely to recur, and studies have shown pulmonary bullae in patients especially in those who have had pneumothorax.…”
Section: Pneumothoraxmentioning
confidence: 99%
“…Four cases of upper lobe fibrosis are reported amongst the 100 cases described by Wood et al (31) and one report of bilateral honeycomb lung (36) exists.…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation